2011
DOI: 10.1111/j.1747-0080.2011.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Don't fall for weight: A systematic review of weight status and falls

Abstract: Aim:To examine the evidence for the contribution of weight status or nutritional status to the incidence of falls. Methods: A systematic review was completed to determine if weight status or nutritional status affects incidence of falls. Inclusion/exclusion criteria were applied to studies published from 2000 which reported weight status and/or nutritional status and falls incidence. Electronic databases searched were CINAHL, MEDLINE, AMED, EMBASE, PUBMED and PsycINFO. Quality assessment and data extraction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The present study found that BMI was not an independent predictor of having a fall or harm following a fall. These findings are in accordance with a systematic review of weight and nutritional status and falls that found limited evidence that being overweight or underweight increased falls incidence despite a higher prevalence of malnutrition in falls populations (Moore & Boltong, 2011). This further suggests the causal association of nutritional status in falls risk and harm from falls is independent of BMI.…”
Section: Author Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study found that BMI was not an independent predictor of having a fall or harm following a fall. These findings are in accordance with a systematic review of weight and nutritional status and falls that found limited evidence that being overweight or underweight increased falls incidence despite a higher prevalence of malnutrition in falls populations (Moore & Boltong, 2011). This further suggests the causal association of nutritional status in falls risk and harm from falls is independent of BMI.…”
Section: Author Manuscriptsupporting
confidence: 90%
“…Instruments used to detect and predict falls risk in hospitalised adult patients vary considerably in their accuracy and effectiveness (Aranda-Gallardo et al, 2013). Some screening tools consider weight status as a potential risk factor for falls, yet there is limited evidence to support the role of weight status alone as an independent predictor of falling (Moore & Boltong, 2011). Malnutrition screening tools have been used to predict risk of falling in community dwelling older adults however use of this method has not been validated in a hospital setting (Tsai & Lai, 2014).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Obesity is associated with structural and functional limitations that have been shown to affect balance and gait patterns (Cau et al, 2014), indicating that obesity may be an independent risk factor for falls (Himes & Reynolds, 2012;Wu et al, 2012). According to a systematic review of weight status and falls, BMI is not a valid predictor of fall risk (Moore & Boltong, 2011). However, there are studies showing a strong correlation between lack of balance and fall risk, especially in the elderly population.…”
Section: Introductionmentioning
confidence: 99%